Optimization of the cholesterol gallstone model in C57BL/6 mice and evaluation of Lactobacillus intervention effects - Cong Wang; Ting Jiang; Lvwang Ye; Mengyan Du; Fang Liu (BMC Gastroenterology)
Abstract Gallstone disease is a common and complex condition, strongly associated with abnormal cholesterol metabolism, changes in bile composition, and impaired gallbladder motility. Recent studies have suggested that the gut microbiota, particularly probiotics like lactic acid bacteria, may play a significant role in the prevention and treatment of cholesterol gallstones. This study aims to optimize the cholesterol gallstone model in C57BL/6 mice and evaluate the effects of Lactobacillus intervention on gallstone formation induced by a high-fat diet. In this study, 8-week-old male C57BL/6 mice were randomly divided into four groups: a high-fat diet + saline group (HF-S), a high-fat diet + probiotic group (HF-P), a normal diet + saline group (ND-S), and a normal diet + probiotic group (ND-P), to assess the effect of probiotics on gallstone formation. The results showed significant differences among the four groups in body weight gain, liver weight, gallstone formation, and histopathology. Based on these preliminary findings, we added two more experimental groups: a 2-week probiotic pretreatment + high-fat diet group (Pre2w-HF) and a 4-week probiotic pretreatment + high-fat diet group (Pre4w-HF), to further investigate the dose-dependence and efficacy of probiotic pretreatment. The results indicated that probiotic intervention significantly reduced the incidence and severity of gallstones induced by a high-fat diet, with the pretreatment groups showing more pronounced effects. Histological analysis also revealed that probiotic intervention reduced inflammation and pathological changes in the liver and gallbladder. This study suggests that probiotics have potential therapeutic value in the prevention and treatment of cholesterol gallstones. Future research should explore the effects of different strains and doses, as well as the underlying mechanisms involved.